2006
DOI: 10.1111/j.1475-2743.2006.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Organic carbon in the silt + clay fraction of Tasmanian soils

Abstract: Organic carbon (C) was measured in the silt + clay fraction of 78 soils from agricultural areas in Tasmania, and the relationship between C in the silt + clay fraction and the percentage by weight of particles in this fraction was compared with similar data for soils from other regions and climates. Most of the cropping soils from Tasmania followed a previously published linear relationship, which is considered an indication of the capacity of soils to store C. The soils which fell the greatest distance below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…In contrast, studies in temperate regions of Canada, China, France, and Germany reported a much lower OC saturation level ranging from 40 to 70% for cropland and pasture soils (Carter et al ., ; Zhao et al ., ; Angers et al ., ; Wiesmeier et al ., ). Only agricultural soils of Tasmania were also close to the potential OC saturation which was related to the cool‐temperate climate and resulting high OC input (Sparrow et al ., ). The finding of a high OC saturation level in strongly degraded steppe soils was unexpected, as a generally high OC sequestration potential was assumed due to massive SOC losses in naturally OC‐rich steppe soils of northern China as a result of intensive cultivation and heavy grazing (Lal, , ; Yu et al ., ; Yan et al ., ; Zhou et al ., ; Li et al ., ; Wiesmeier et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, studies in temperate regions of Canada, China, France, and Germany reported a much lower OC saturation level ranging from 40 to 70% for cropland and pasture soils (Carter et al ., ; Zhao et al ., ; Angers et al ., ; Wiesmeier et al ., ). Only agricultural soils of Tasmania were also close to the potential OC saturation which was related to the cool‐temperate climate and resulting high OC input (Sparrow et al ., ). The finding of a high OC saturation level in strongly degraded steppe soils was unexpected, as a generally high OC sequestration potential was assumed due to massive SOC losses in naturally OC‐rich steppe soils of northern China as a result of intensive cultivation and heavy grazing (Lal, , ; Yu et al ., ; Yan et al ., ; Zhou et al ., ; Li et al ., ; Wiesmeier et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In cropland soils of Australia, a lower C saturation of around 35% was determined, which was related to low precipitation and high temperatures (Hassink, 1997;Chan, 2001). In contrast, agricultural soils in Tasmania under a cool, temperate climate were close to or even exceeded the potential C saturation (Sparrow et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the potential C saturation of the fine fraction and the actual measured C content of this fraction corresponds to the C saturation deficit or, in other words, the C sequestration potential. Hassink's approach was used in several experimental studies to estimate the degree of C saturation in cultivated soils (Chan, ; Six et al ., ; Carter et al ., ; Conant et al ., ; Sparrow et al ., ; Zhao et al ., ). However, these studies included only a limited number of investigated locations, thus the results are not suitable to derive comprehensive conclusions for larger (landscape) scales.…”
Section: Introductionmentioning
confidence: 99%
“…Fluvially-dominated sites are found to have finer sediment sizes relative to marine-dominated sites [ 5 ]. Decreased grain size in sediments causes the sediment organic carbon to increase [ 5 , 43 ], owing to clay particles binding carbon molecules and reducing microbial breakdown [ 44 ].…”
Section: Discussionmentioning
confidence: 99%